Impact of case-based learning on critical thinking dispositions in Chinese nursing education: a systematic review and meta-analysis - Xiang, Yunlu; Liu, Dong; Liu, Liang; Liu, I-Chun; Wu, Lanka; Fan, Hao (Frontiers in Medicine, 2025)
BackgroundCase-based learning (CBL) is recognized for its potential to enhance critical thinking in nursing education. This meta-analysis aimed to assess the impact of CBL alone or in combination with other methods on improving critical thinking dispositions among nursing students in China.MethodsA systematic search was conducted in databases including PubMed, Embase, Cochrane Library, CINAHL and China National Knowledge Infrastructure from inception of the databases through June 1, 2024. Studies that utilized the Chinese Version of Critical Thinking Dispositions Inventory (CTDI-CV) and compared CBL with traditional teaching methods were included. Random-effects models were used to pool the mean differences (MD) in critical thinking scores, and subgroup analyses were performed based on participant types and intervention methods.ResultsThirteen studies involving 1,396 participants were included. The pooled results indicated a significant improvement in critical thinking dispositions (MD = 26.39, 95% CI: 18.71 to 34.06). Subgroup analysis revealed that nursing interns and combinations of CBL with problem-based learning (PBL) reported higher improvements. Secondary outcomes showed significant gains in both theoretical knowledge and operational skills, with heterogeneity observed across studies (I2 > 79%). The Egger’s test (p = 0.95) suggested no significant publication bias.ConclusionCBL significantly enhances critical thinking among nursing students in China, particularly when integrated with PBL. Despite the observed heterogeneity, the findings support the incorporation of CBL into nursing curricula to foster critical analytical skills. Further research should explore the contextual factors that affect the variability in outcomes.